2012
DOI: 10.1155/2012/265714
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin Inhibits Mucus Hypersecretion from Airway Epithelial Cells

Abstract: To examine the in vivo effects of the 15-member macrolide, azithromycin (AZM), on mucus hypersecretion, we induced hypertrophic and metaplastic changes of goblet cells in rat nasal epithelium by intranasal instillation of ovalbumin (OVA) in OVA-sensitized rats, or by intranasal lipopolysaccharides (LPS) instillation. Oral administration of AZM (5–10 mg/kg) or clarithromycin (CAM, 5–10 mg/kg) significantly inhibited OVA- and LPS-induced mucus production, whereas josamycin (JM) or ampicillin (ABPC) showed no eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
(37 reference statements)
3
22
1
1
Order By: Relevance
“…Our results showed that AZM inhibited total mucin, and MUC5AC gene and protein expression in NCI-H292 cells. This is in line with previous reports [4,17,18]. …”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our results showed that AZM inhibited total mucin, and MUC5AC gene and protein expression in NCI-H292 cells. This is in line with previous reports [4,17,18]. …”
Section: Discussionsupporting
confidence: 94%
“…One previous study reported that josamycin (a 16-membered macrolide) did not inhibit MUC5AC production [4]. However, in the present study, we found that MDM (a 16-membered macrolide) inhibited mucin secretion from airway epithelial cells similarly to AZM (a 15-membered macrolide).…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…MUC5AC mRNA expression was also significantly lower in macrolide-treated NCI-H292 cells and human nasal epithelial cells than controls [76]. Significantly, these results for CAM and AZM have been reproduced in a separate study [77]. The reduced MUC5AC mRNA transcription was suggested to be via macrolide inhibition of IL-13 signalling pathways [78].…”
Section: Inhibition Of Mucin Secretionmentioning
confidence: 99%